Differential roles of hydrogen peroxide and superoxide in mediating IL-1-induced NF-kappaB activation and iNOS expression in bovine articular chondrocytes - Mendes, Alexandrina Ferreira (2003)
Our previous studies showed that reactive oxygen species (ROS) are required for the pro-inflammatory cytokine interleukin-1beta (IL-1) to induce the activity of the Nuclear transcription Factor-kappaB (NF-kappaB) and the expression of the inducible isoform of the nitric oxide synthase (iNOS) in bovine articular chondrocytes. This study aimed at elucidating the role of hydrogen peroxide (H2O2) and the superoxide radical, two major ROS, in mediating those IL-1-induced responses. The results obtained show that chondrocytes produce both H2O2 and superoxide radical in response to IL-1. Treatment of the chondrocyte cultures with H2O2 alone did not induce NF-kappaB activation or iNOS expression. Addition of H2O2 simultaneously with IL-1 did neither enhance nor inhibit NF-kappaB activation and iNOS expression, relatively to treatment with IL-1 alone. Accordingly, treatment with catalase did not inhibit those IL-1-induced responses. Treatment with superoxide dismutase, however, effectively prevented IL-1-induced IkappaB-alpha degradation and iNOS expression. Taken together, the results obtained indicate that superoxide mediates IL-1-induced IkappaB-alpha degradation and the consequent NF-kappaB activation and iNOS expression in chondrocytes, whereas H2O2 does not seem to participate in those IL-1-induced responses. In conclusion, the present study identifies the superoxide radical as the ROS involved in mediating the IL-1-induced signaling pathway that leads to NF-kappaB activation and to the expression of NF-kappaB-dependent genes in bovine articular chondrocytes. © 2003 Wiley-Liss, Inc.